2006
DOI: 10.1007/s00203-006-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the type III export signal of the flagellar hook scaffolding protein FlgD of Escherichia coli

Abstract: Transport of flagellar structural proteins beyond the cytoplasmic membrane is accomplished by a type III secretory pathway [flagellar type III secretion system (fTTSS)]. The mechanism of substrate recognition by the fTTSS is still enigmatic. Using the hook scaffolding protein FlgD of Escherichia coli as a model substrate, it is demonstrated that the export signal is contained within the N-terminal 71 amino acids of FlgD. Analysis of frame-shift mutations and alterations of the nucleotide sequence suggest a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Certain studies suggested that the signal sequence is found at the mRNA level (1,25) or that the combination of an Nterminal signal and a structural element in the mRNA is required (3). On the other hand, a growing number of data support that the signal is contained at the protein level, and it is located at or near the N terminus (6,12,17,19,22,36,39,40). The identified signal sequences of different flagellar proteins, however, do not show any significant sequence similarity, which indicates that determinants should be at higher than the primary structural level.…”
Section: Vol 76 2010mentioning
confidence: 99%
See 2 more Smart Citations
“…Certain studies suggested that the signal sequence is found at the mRNA level (1,25) or that the combination of an Nterminal signal and a structural element in the mRNA is required (3). On the other hand, a growing number of data support that the signal is contained at the protein level, and it is located at or near the N terminus (6,12,17,19,22,36,39,40). The identified signal sequences of different flagellar proteins, however, do not show any significant sequence similarity, which indicates that determinants should be at higher than the primary structural level.…”
Section: Vol 76 2010mentioning
confidence: 99%
“…For example, residues 38 to 58 of Caulobacter crescentus flagellar hook protein were found to be essential for secretion (19). Similarly, it has been demonstrated that the export signal of the hook scaffolding protein FlgD of Escherichia coli is located exclusively within the N-terminal 71 amino acids (40). Single amino acid substitutions within the N-terminal region of the anti-sigma factor FlgM (6), which is also exported by the flagellum-specific export apparatus, severely impair its export.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…XC1894 is a flagellar hook-capping protein from X. campestris Figure 2 shows the multiple sequence alignment of X. campestris XC1894 with the two well-studied FlgD sequences from E. coli 17,18 and Salmonella typhimurium. 7 As can be seen from the alignment, XC1894 exhibits high sequence identity (36.9% and 37.6%) and similarity (49.0% and 48.6%) with the E. coli and S. typhimurium FlgD sequences, respectively.…”
Section: Xc1894 Exhibits N-terminal Cleavagementioning
confidence: 99%
“…A similar behavior occurs in H. pylori FlgD, whose crystals have been grown by our group. A study of FlgD from E. coli (Weber-Sparenberg et al, 2006) indicated that the first 71 N-terminal residues represent a signal for the export into the flagellar channel. The superimposition of FlgD structures is given within Fig.…”
Section: The Hookmentioning
confidence: 99%